2016
DOI: 10.1093/omcr/omw091
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic symptoms as the only manifestation of B12deficiency in a young patient with normal hematocrit, MCV, peripheral blood smear and homocysteine levels

Abstract: B12 deficiency is associated with several neurological manifestations. It is well documented that neurologic symptoms due to B12 deficiency may sometimes present in the absence of anemia. However, in most cases there are several indicating factors like megaloblastic changes in complete blood count, hypersegmentated neutrophils or macroovalocytes in peripheral blood smear and abnormal homocysteine levels. In this report, we describe a case of a 32-year-old man with neurological symptomatology as the only manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“… 25 , 29 Neurologic manifestations may be the earliest and only manifestation of vitamin B12 deficiency. 30 The commonly recognized neurologic findings may include a myelopathy with or without an associated neuropathy, optic neuropathy (impaired vision, optic atrophy, centrocecal scotomas), paresthesias without abnormal signs, and neuropsychiatric disturbances. The best characterized neurologic manifestation of vitamin B12 deficiency is a myelopathy that has commonly been called subacute combined degeneration.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 29 Neurologic manifestations may be the earliest and only manifestation of vitamin B12 deficiency. 30 The commonly recognized neurologic findings may include a myelopathy with or without an associated neuropathy, optic neuropathy (impaired vision, optic atrophy, centrocecal scotomas), paresthesias without abnormal signs, and neuropsychiatric disturbances. The best characterized neurologic manifestation of vitamin B12 deficiency is a myelopathy that has commonly been called subacute combined degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the GM composition differed according to the level of alanine aminotransferase (ALT) in HBV patients[ 80 , 81 ]. Desulfovibrio had a positive correlation, while Acidaminococcus showed a negative correlation with high ALT level[ 81 ].…”
Section: Pscmentioning
confidence: 99%
“…Furthermore, the GM composition differed according to the level of alanine aminotransferase (ALT) in HBV patients[ 80 , 81 ]. Desulfovibrio had a positive correlation, while Acidaminococcus showed a negative correlation with high ALT level[ 81 ]. Lu et al [ 16 ] found a significantly decreased ratio of Bifidobacteriaceae/Enterobacteriaceae (B/E) in cirrhotic HBV positive patients, while Yun et al [ 72 ] observed no difference in the B/E ratio in non-cirrhotic HBV patients with positive HBsAg and normal or high ALT.…”
Section: Pscmentioning
confidence: 99%
“…Gut microbes, such as Bacteroides fragilis , Enterococcus faecium , Enterobacter agglomerans , and Eubacterium lentum , produce vitamin K2, which can reduce the risk of atherosclerosis and coronary heart diseases [ 51 , 52 ]. The gut microbiota can also produce vitamin B (B5 and B12) that are important for the functions of the nervous system, and their deficiency often associated with neurologic dysfunction, psychiatric and gastrointestinal, malabsorption, and insomnia disorders [ 53 , 54 ]. The gut microbiota also plays a vital role in the metabolism of bile acids to secondary bile acids, which include deoxycholic acid (DCA), hyodeoxycholic acid (HDCA), and lithocholic acid (LCA).…”
Section: Gut Microbiota and Healthmentioning
confidence: 99%